Horses and worthwhile causes: Exploring equine-assisted learning at Dune Lakes Horse Inspired Learning Centre in Aotearoa New Zealand - Napan K; Lietz R (Aotearoa New Zealand Association of Social Workers)
INTRODUCTION: Equine-assisted therapies and trauma-informed interventions have become increasingly popular with a growing literature suggesting that people can deeply relate to experiential work with horses, where silence, emotional growth, reflection and acceptance are prioritised over talking about problems. APPROACH: This research, undertaken at a rural learning and retreat centre near Auckland in Aotearoa New Zealand, examines how practitioners tailor equine-assisted interventions (EAI) and sheds light into values, theories and frameworks that underpin their work. The study is based on personal and professional experiences of four practitioners who engage in equineassisted learning. FINDINGS AND APPLICATION: Findings are drawn from the thematic analysis of the transcripts of four semi-structured interviews, highlighting the process of facilitating posttraumatic growth in a professional, supportive and client-centred environment involving a facilitator, a horse, and a person keen to improve the quality of their life. Application of this modality, particularly when working with clients with complex trauma, is explored with a special emphasis on the relevance of involvement of animals in social work practice.
Keywords: animals in social work; horse-assisted intervention; Horse-assisted learning